Non-linear Isotherm Models, Cadmium Kinetics, and Biosorption Thermodynamics of Dried Biomass of Native Aphanothece sp. in a Batch System - Satya, Awalina; Harimawan, Ardiyan; Sri Haryani, Gadis; Setiadi, Tjandra (ITB Journal Publisher, LPPM ITB, 2017)
Dried biosorbent was prepared from Aphanothece sp. cyanobacteria harvested from a photobioreactor system fed with atmospheric carbon dioxide. Cadmium-ion biosorption of the prepared biosorbent from aqueous solution was characterized by non-linear (Langmuir, Freundlich and DubininâRadushkevich) isotherms, non-linear kinetics (pseudo first-order and pseudo second-order) and thermodynamic analysis. The optimum conditions were pH 8.0, 30Â°C, 0.1 g/L biomass, and 60 min contact time. The biosorption efficiencies exceeded 90%. The low-range data (initial Cd concentration C0 = 1.09â6.23 mg/L) and high-range data (C0 = 5.41â83.07 mg/L) were best fitted to the Langmuir model, with maximum uptake capacities of 12.01 and 187.5 mg/g (R2 = 0.995 and 0.996). In the DubininâRadushkevich isotherm model, the mean biosorption energy was 12.91 kJ/mol, suggesting that ion exchange was the working mechanism. The biosorption apparently followed pseudo second-order kinetics (R2 = 0.994â0.999; k2 = 2.04 E-03 to 3.86 E-02 g/mg min). The biosorption process was energetically feasible (âG0 = â13.47ââ8.88 kJ/mol), exothermic (âH0 = â74.82 kJ/mol) and tended to become more ordered (âS0 = â0.204 kJ/mol K) towards the end of the process. The biosorbent was reusable through three adsorption/desorption cycles in 1 M HCl.